80.8k views
11 votes
What is true about the sum of the two polynomials?

6s2t – 2st2

4s2t – 3st2
What is the additive inverse of the polynomial –9xy2 + 6x2y – 5x3?

User Lulyon
by
4.8k points

1 Answer

6 votes

Answer:

f'(x) = -f(x) = 9xy² - 6x²y + 5x³

Explanation:

f(x) = –9xy² + 6x²y – 5x³

additive inverse: f'(x) = -f(x) = 9xy² - 6x²y + 5x³

f(x) + f'(x) = f(x) -f(x) = (–9xy² + 6x²y – 5x³) + (9xy² - 6x²y + 5x³) = 0

User Kaplievabell
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.